Environmentally Friendly Composites from Agricultural Residue Biomass for Lightweight Applications in New Generation Structures: A Review - Murugesan Palaniappan; Sivasubramanian Palanisamy; Borhen Louhichi; Nadir Ayrilmis; Thulasi mani Murugesan (BioResources)
The increasing global demand for sustainable materials has spurred extensive research into biopolymer-based composites derived from agricultural residue biomass. These materials offer an eco-friendly alternative to petroleum-based composites, addressing environmental pollution, resource depletion, and the need for low-density materials in sectors such as automotive, aerospace, packaging, and construction. This research focused on low-density bio-based composites as sustainable options for lightweight applications in automotive, aerospace, packaging, and construction. It highlights the use of agricultural residue and discontinuous binder systems to reduce density, as well as manufacturing techniques that improve structural efficiency. It emphasizes critical composite properties such as mechanical strength, thermal behavior, water resistance, biodegradability, and lightweight characteristics. The influence of fiber content and processing parameters on overall performance is also discussed. In addition, the review highlights major challenges, including scalability, cost-effectiveness, and long-term stability and proposes future research directions focused on durability enhancement, production efficiency, and commercial viability. Overall, this work underscores the transformative potential of agricultural residue-derived bio composites in advancing sustainable, high-performance materials for lightweight and eco-conscious construction and industrial applications.